“We’re getting older and things are changing”: Qualitatively exploring older adults’ everyday experiences in relation to early changes in mobility - Olivia Chivers; Lynn Rutledge; Marla Beauchamp; Brenda Vrkljan; Evelyne Durocher (PLoS ONE, 2026)
Mobility can require skills from ambulating to driving and using public transportation. The onset of mobility impairments has been linked to reductions in physical function, social participation, health status and quality of life. We qualitatively explore how early changes in mobility are experienced by older persons and how such changes shape performance and engagement in everyday activities in later life. We conducted semi-structured interviews with 25 community-dwelling older persons and through thematic analysis identified four themes in the data. Participants described perceptions that everyday activities require more energy, a need for increased awareness and mitigation of risks when doing activities, a “use it or lose it” approach to maintaining mobility and comparisons between themselves and others. The results suggest that addressing expectations of aging, promoting engagement in meaningful activities, particularly those that enhance mobility, and increasing awareness of early changes in mobility are critical to maintaining engagement in later life.